A simulator evaluation of in-vehicle human machine interfaces for eco-safe driving. (December 2018) - Vaezipour, Atiyeh; Rakotonirainy, Andry; Haworth, Narelle; Delhomme, Patricia
Highlights: In-vehicle HMI to improve both eco-driving and safe driving in one integrated system. Driving simulator evaluation of advisory vs feedback vs advice/feedback in-vehicle HMI. Greater levels of usability and satisfaction are associated with the 'advice only' HMI. Eco-safe in-vehicle HMI combining advice and feedback messages is more effective. Advice/feedback in-vehicle HMI reduced fuel consumption by 6.7% Abstract: In-vehicle human machine interfaces (HMI) represent a promising approach for informing drivers what they should do to adopt an eco-safe driving style, which is associated with reduced fuel consumption and improved safety. However, there is limited understanding of the driver acceptance of various types of in-vehicle HMIs and the impact of such systems on driving behaviour. Forty drivers participated in a simulated driving experiment to evaluate three variations of an eco-safe in-vehicle HMI: visual advice only; visual feedback only; or visual advice and feedback. To evaluate the impact of the different HMIs, subjective and objective measures were analysed, including fuel consumption, eco-safe driving behaviour, driver acceptance, and workload. Results indicate that all system types were associated with the relatively high levels of driver acceptance, with the advice only system accepted the most. While all system types produced relatively low levels of workload for drivers, systems involving feedback significantly increased the workload associated with using the interface. The findings suggest that the combined advice and feedback system has the potential to simultaneously reduce fuel consumption and improve eco-safe driving behaviour. Specifically, both advice and feedback appeared to be critical in encouraging positive changes in eco-safe driving behaviour. Our contribution can inform the design and development of future in-vehicle HMIs to improve eco-safe driving style that are accepted by drivers and have minimal adverse impacts on driver workload.